Effect of Dividend Policy on Stock Price in LQ45 Companies - Fida Oktafiani; Sukma Irdiana; Irwan Moridu; Fandy Latuni; Revi Sesario (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze effect of dividend policy on stock price in LQ45 companies. This research uses a causal research type with a quantitative approach. The population in this study are LQ45 companies listed on the Indonesia Stock Exchange for the 2017-2021 period as many as 64 companies. Based on the selection of criteria that meet the requirements to be selected as many as 30 companies as a sample. The method of data analysis in this study used simple linear regression analysis. The results of the study show that dividend policy has positive and significant effect on stock price.